Differences in methodologies of measuring the prevalence of oral mucosal lesions in children and adolescents - D. L. C. FURLANETTO, A. CRIGHTON, & G. V. A. TOPPING (IAPD and Blackwell, 2006)
Understanding the distribution, aetiology, natural history and epidemiology of oral mucosal pathologies is essential to promote primary prevention,early diagnosis, prompt treatment and the provision of appropriate health services [1].